Media Sinema Komedi untuk Meningkatkan Sikap Respek Siswa SMP - Riki Anggrian; Carolina L. Radjah; Im. Hambali (Pascasarjana Universitas Negeri Malang, 2021)
Abstract: Comedy cinema media is an audio-visual media with comedy content that is fun but meaningful for students. This comedy cinema media is used in educational cinema techniques as a stimulant for student learning to increase respect. This study aims to develop a guidance product with educational cinema techniques providing comedy cinema to increase the respect of junior high school students, which is developed through a research and development model. The resulting product gets a very high score from expert tests and potential product users based on its acceptability criteria. So that this development product can be used by counselors to increase the attitude of respect for junior high school students. Abstrak: Media sinema komedi merupakan media dalam bentuk audio-visual dengan konten komedi yang menggembirakan namun bermakna bagi peserta didik. Media sinema komedi ini digunakan dalam teknik sinema edukasi sebagai stimulan belajar siswa untuk meningkatkan sikap respek. Penelitian ini bertujuan untuk mengembangkan produk panduan bimbingan dengan teknik sinema edukasi bermediakan sinema komedi untuk meningkatkan sikap respek Siswa SMP, yang dikembangkan melalui model penelitian dan pengembangan. Produk yang dihasilkan mendapatkan skor sangat tinggi  dari uji ahli dan calon pengguna produk berdasarkan kriteria akseptabilitasnya. Sehingga produk pengembangan ini dapat digunakan oleh konselor untuk meningkatkan sikap respek siswa SMP.